Characteristics of Medicare Advantage and Fee-for-Service Beneficiaries Upon Enrollment in Medicare at Age 65. Issue 3 (July 2016) - Miller, Eric A.; Decker, Sandra L.; Parker, Jennifer D.
Abstract : Previous research has found differences in characteristics of beneficiaries enrolled in Medicare fee-for-service versus Medicare Advantage (MA), but there has been limited research using more recent MA enrollment data. We used 1997-2005 National Health Interview Survey data linked to 2000-2009 Medicare enrollment data to compare characteristics of Medicare beneficiaries before their initial enrollment into Medicare fee-for-service or MA at age 65 and whether the characteristics of beneficiaries changed from 2006 to 2009 compared with 2000 to 2005. During this period of MA growth, the greatest increase in enrollment appears to have come from those with no chronic conditions and men.